An analysis of urban regeneration in the historical context (Case study: Dezful city) - Nahid Keshavarz; Hamidreza Joodki; Ali Nourikermani (تحقیقات کاربردی علوم جغرافیایی)
The historical district of cities is a valuable architectural and urban heritage, reflecting the cultural, economic, and social dimensions of the people who, throughout history, have lived in this part of the city and shaped its cultural identity. These areas have witnessed a decline in urban development, and the limited efforts made toward their improvement or reconstruction have been inadequate. The aim of this analytical research is to explore urban regeneration in the historical (old) fabric of Dezful city. The research method employed in this study is a survey-based approach. The statistical population of the present study includes all residents of the historical fabric of Dezful, which, according to the latest census by the Statistical Center of Iran, has a population of approximately 29,277 people. To achieve a logical sample size, Cochran's formula was used, resulting in the selection of 384 samples through stratified random sampling. The primary data collection tool in this research is a questionnaire; however, due to the specialized nature of the questionnaire, interview and observation methods were also utilized to complement the questionnaire data. The results derived from the SWOT and QSPM models indicate that, out of the five final strategies for the regeneration of the historical fabric of Dezful, the top two strategies belong to offensive strategies. Accordingly, studying and designing the possibility of creating pedestrian pathways in the historical fabric—considering the growing public interest in cultural and historical tourism—and utilizing the space along the Dez River for green space development and designing a green corridor along the river and historical fabric can be considered the most important offensive strategies.